An Update on Animal Models for Severe Acute Respiratory Syndrome Coronavirus 2 Infection and Countermeasure Development - Zhang, Liang; Chen, Shuaiyin; Zhang, Weiguo; Yang, Haiyan; Jin, Yuefei; Duan, Guangcai (Frontiers in Microbiology, 2021)
Coronavirus Disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a pandemic since March 2020 and led to significant challenges to over 200 countries and regions all over the world. The establishment of highly pathogenic coronavirus animal model is beneficial for the study of vaccines and pathogenic mechanism of the virus. Laboratory mice, Syrian hamsters, Non-human primates and Ferrets have been used to establish animal models of emerging coronavirus infection. Different animal models can reproduce clinical infection symptoms at different levels. Appropriate animal models are of great significance for the pathogenesis of COVID-19 and the research progress related to vaccines. This review aims to introduce the current progress about experimental animal models for SARS-CoV-2, and collectively generalize critical aspects of disease manifestation in humans and increase their usefulness in research into COVID-19 pathogenesis and developing new preventions and treatments.